Analisis Break Even Point Sebagai Alat Perencanaan Laba Pada Rumah Makan Berkah Cahaya di Desa Kerang Kecamatan Batu Engau - Rusmiati, Rusmiati; Syam, M Yunus; Amalia, Agustin Nur (ARBITRASE: Journal of Economics and Accounting, 2022)
This research was conducted with the aim of (1) knowing the amount of rupiah for grilled chicken and beef bone soup that must be obtained to reach the break even point at the Berkah Cahaya Restaurant in Kerang Village, Batu Engau District. (2) Knowing the number of servings of grilled chicken and beef bone soup consumed must be sold to reach the break even point at the Berkah Cahaya Restaurant in Kerang Village, Batu Engau District (3) knowing the amount of sales in order to achieve the planned profit at the Berkah Cahaya Restaurant in Kerang Village, Batu Engau District. Break even point analysis or break even point which is an analytical technique to study the relationship between total costs, expected profit and sales volume. In general, this analysis also provides information regarding the margin of safety which is useful as an indication and illustration to management of how much a decline in sales can be estimated so that the business being carried out does not suffer a loss. Rumah Makan Berkah Cahaya is a small trading business that sells food and drinks. The types of products are grilled chicken and beef bone soup. The results of the analysis are as follows: BEP in 2021 for grilled chicken is IDR 69,878,371 and beef bone soup is IDR. 159,084,803 The number of portions that must be sold so that the Berkah Cahaya Restaurant does not suffer losses in 2012 for grilled chicken was 2,795 portions while for beef bone soup as many as 6,363 portions. The sales that must be achieved in order for the roasted chicken to earn a profit of IDR 100,000,000 is IDR 303,523,231 while for the beef bone soup in order to obtain a profit of IDR 80,000,000, the sales must reach IDR. 584,616,718.